The moderating effect of appearance on the impact of performance rankings in the live streaming market - Chen, Yasheng; Huang, Xian; Zhao, Sijia (Frontiers in Psychology, 2022)
The live streaming market is becoming increasingly competitive, and relative performance information regarding broadcasters is available to all participants in the live streaming industry, exacerbating the level of competition. Using data from 42,166 live streams by 293 broadcasters, we investigated two benefits of relative performance information in relation to the live streaming business and how these effects vary when the broadcaster appears competent, trustworthy, likable, or attractive. On the basis of economic and social comparison theory, as well as insights from the herd behavior and beauty premium literature, we predicted that relative performance information can improve live streaming performance by either increasing broadcaster effort (the effort-eliciting effect) or encouraging viewer participation (the informational effect), with these effects being stronger when broadcasters look more competent, trustworthy, likable, or attractive. To test our predictions, we performed correlation analyses, mediation analyses, and moderated mediation analyses using SPSS PROCESS Macro. The empirical results supported our predictions. The findings of this study contribute to the live streaming literature by demonstrating that providing relative performance information in the live streaming business can yield both effort-eliciting and informational benefits.